2021
DOI: 10.1111/dom.14532
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of liraglutide in type 1 diabetes by baseline characteristics in the ADJUNCT ONE and ADJUNCT TWO randomized controlled trials

Abstract: Aim: To evaluate 26 weeks of liraglutide treatment in type 1 diabetes (T1D) by subgroups in the ADJUNCT ONE and ADJUNCT TWO trials.Materials and Methods: ADJUNCT ONE and ADJUNCT TWO were randomized controlled phase 3 trials in 1398 and 835 participants with T1D treated with liraglutide (1.8, 1.2, or 0.6 mg) or placebo (adjuncts to insulin). This post hoc analysis evaluated treatment effects by subgroups: HbA1c (< or ≥8.5%), body mass index (BMI; < or ≥27 kg/m 2 ), and insulin regimen (basal bolus or continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…A post hoc analysis of the studies revealed that the efficacy of liraglutide in reducing HbA 1c did not depend on baseline body weight and glycemic control subgroups. However, residual β-cell function was associated with a significant impact on HbA 1c reduction and the risk of hypoglycemia [69]. Adverse events were higher in the liraglutide groups and were mainly related to the gastrointestinal system.…”
Section: Glp1-receptor Agonistsmentioning
confidence: 93%
“…A post hoc analysis of the studies revealed that the efficacy of liraglutide in reducing HbA 1c did not depend on baseline body weight and glycemic control subgroups. However, residual β-cell function was associated with a significant impact on HbA 1c reduction and the risk of hypoglycemia [69]. Adverse events were higher in the liraglutide groups and were mainly related to the gastrointestinal system.…”
Section: Glp1-receptor Agonistsmentioning
confidence: 93%
“…For anti-IL-21 antibody targeting IL-21, early clinical trials did not reflect significant safety risks or significant changes in laboratory safety parameters [98]. Glucagon-like peptide-1 receptor (GLP-1R) agonists liraglutide has been suggested to preserve functional beta cells by reducing metabolic stresses and preventing apoptosis [99]. Therefore, combined treatment could enable beta-cell survival with a reduced risk of complications compared with traditional immunomodulation.…”
Section: Combination Immunomodulatory and Beta-cell Therapymentioning
confidence: 99%
“…These beneficial effects observed in type 2 diabetes have encouraged some physicians to initiate GLP1-RA and/or SGLT2i in people with type 1 diabetes. Previous studies evaluated the efficacies and safety of GLP1-RA and SGLT2i therapy in individuals with type 1 diabetes, but the combination of the medications is not yet described [14][15][16][17]. In clinical trials, the addition of GLP1-RA liraglutide to insulin led to a reduction in glycated hemoglobin (HbA1c), body weight, and total insulin dose; however, episodes of hypoglycemia or hyperglycemia with ketosis increased [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies evaluated the efficacies and safety of GLP1-RA and SGLT2i therapy in individuals with type 1 diabetes, but the combination of the medications is not yet described [14][15][16][17]. In clinical trials, the addition of GLP1-RA liraglutide to insulin led to a reduction in glycated hemoglobin (HbA1c), body weight, and total insulin dose; however, episodes of hypoglycemia or hyperglycemia with ketosis increased [14,15]. Similarly, adding SGLT2i dapagliflozin to insulin therapy was associated with improved HbA1c and reduced body weight and insulin dose [16][17][18].…”
Section: Introductionmentioning
confidence: 99%